2015
DOI: 10.2174/1573399811666150401104515
|View full text |Cite
|
Sign up to set email alerts
|

Possible Underestimation by Sports Medicine of the Effects of Early Physical Exercise Practice on the Prevention of Diseases in Adulthood

Abstract: In modern society, combatting cardiovascular and metabolic diseases has been highlighted as an urgent global challenge. In recent decades, the scientific literature has identified that behavioral variables (e.g. smoking, unhealthy diet and physical inactivity) are related to the development of these outcomes and, therefore, preventive actions should focus on the promotion of physical exercise practice and a healthy diet, as well as combatting the smoking habit from an early age. The promotion of physical exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…In recent decades, great attention has been paid to the prevention of cardiovascular diseases in adulthood, while growing scientific literature has pointed out that cardiovascular and metabolic diseases that develop in adulthood have their origins in early life (Fernandes, Spiguel, Cayres, Codogno, & Lira, ; Lira, Rosa Neto, Antunes, & Fernandes, ). Therefore, behavioral variables in pediatric populations have been widely investigated, mainly because unhealthy behaviors track from early life to adulthood (Healy, Matthews, Dunstan, Winkler, & Owen, ; Juonala, Magnussen, et al., ; Pereira, Ki, & Power, ) and a large variety of cardiovascular and metabolic outcomes have been linked to the adoption of unhealthy behaviors.…”
mentioning
confidence: 99%
“…In recent decades, great attention has been paid to the prevention of cardiovascular diseases in adulthood, while growing scientific literature has pointed out that cardiovascular and metabolic diseases that develop in adulthood have their origins in early life (Fernandes, Spiguel, Cayres, Codogno, & Lira, ; Lira, Rosa Neto, Antunes, & Fernandes, ). Therefore, behavioral variables in pediatric populations have been widely investigated, mainly because unhealthy behaviors track from early life to adulthood (Healy, Matthews, Dunstan, Winkler, & Owen, ; Juonala, Magnussen, et al., ; Pereira, Ki, & Power, ) and a large variety of cardiovascular and metabolic outcomes have been linked to the adoption of unhealthy behaviors.…”
mentioning
confidence: 99%
“…Children and adolescents have become important targets of public health because individual healthrelated psychology and behavior are formed in early childhood (10). Previous review has indicated that early healthy practice can be protective for metabolic outcomes in adults (11,12). Psychosocial exposures in childhood, which much in uenced on creation of sense of value, can also be determinants of lifelong predilection to metabolic disease in adulthood (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial part of the call for physical activity promotion from early ages is related to the high prevalence of childhood obesity worldwide, which has been considered the main risk factor and precursor of chronic diseases [34]. However, the potential pathways by which different types of phys-ical activity performed in early ages could lead to short-, medium-, and long-term effects on health are still in discussion [11].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sports practice in childhood and metabolic risk in adolescence was mediated by physical activity, obesity, and cardiorespiratory fitness. concerning a possible direct effect of sports practice in childhood on chronic diseases during later ages [11,32]. In a retrospective study, Fernandes and Zanesco [10] found that subjects who practiced exercise during childhood and/or adolescence were less likely to present chronic diseases in adulthood regardless of habitual physical activity practice.…”
Section: Introductionmentioning
confidence: 99%